Investigation on novel desiccant wheel using wood pulp fiber paper with high coating ratio as matrix. (1st June 2019) - Wu, X.N.; Ge, T.S.; Dai, Y.J.; Wang, R.Z.
Abstract: A kind of wood pulp fiber paper (WPFP) was proposed as candidate for the matrix of desiccant wheel. Silica gel was coated on WPFP by impregnation method and the corresponding coating ratio was obtained and analyzed. Then the thermal conductivity, pore structure and adsorption/desorption performances of WPFP coated with silica gel were tested and analyzed. The results indicated that the WPFP has high coating ratio for silica gel due to its hydrophilic characteristic. The thermal conductivity of WPFP coated with silica gel after the first coating increases obviously compared with raw WPFP and reaches to 0.1292 W/(m⋅K). In addition, the WPFP coated with silica gel after the first coating has high specific surface area and its maximal adsorption quantity for water vapor can be 0.240  g/g. Finally, the DCOP of the desiccant wheel using WPFP as matrix obtained by numerical simulation can be 1.75 under the given working condition that the temperature of regeneration air is set as 90 °C and the inlet condition of process air is set as 34.3 °C and 56.2% RH. It is indicated that the desiccant wheel using WPFP as matrix can meet the requirement of air dehumidification and save energy by 7.35% simultaneously. Highlights: Novel desiccant wheel using WPFP with high coating ratio as matrix was proposed. WPFP belongs to hydrophilic material and has high coating ratio for silica gel. The water vapor adsorption quantity of WPFP can be fitted well by D-A equation. The DCOP of the desiccant wheel with WPFP as matrix can be 1.75.